2013
DOI: 10.7150/ijbs.6291
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine-Like Factor 1 (CLFK1) Is Over-Expressed in Patients with Atopic Dermatitis

Abstract: Background: Human chemokine-like factor 1 (CKLF1), a recently discovered chemokine, has a broad spectrum of biological functions in immune-mediated diseases. It is highly expressed on Th2 lymphocytes and is a functional ligand for human CCR4. CKLF1 has a major role in the recruitment and activation of leucocytes, which plays an important role in the pathogenesis of allergic diseases. The present study was designed to determine the expression of CKLF1 in skin and serum in patients with atopic dermatitis (AD).Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Previous studies have verified that CKLFs have multiple activities, such as attract human neutrophils, lymphocytes, and monocytes and stimulate the proliferation and differentiation of murine skeletal myoblast cells. CKLF1 has shown broad chemotactic activities on leukocytes and plays essential roles in inflammatory and autoimmune diseases (12)(13)(14)(15)(16)(17). However, the relationship between CKLF1 and cancer is uncertain, particularly HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have verified that CKLFs have multiple activities, such as attract human neutrophils, lymphocytes, and monocytes and stimulate the proliferation and differentiation of murine skeletal myoblast cells. CKLF1 has shown broad chemotactic activities on leukocytes and plays essential roles in inflammatory and autoimmune diseases (12)(13)(14)(15)(16)(17). However, the relationship between CKLF1 and cancer is uncertain, particularly HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological changes have been observed in the skin of EC-sensitized mice that include local inflammation, epidermal thickening, hyperplasia, inflammatory cell infiltration and slight hyper-keratosis (Karki et al 2012;Yang et al 2013). Histopathological results from the present work showed EC sensitization of mice could induce the above-mentioned skin lesions and pathological changes in the intestines as found in food allergy.…”
Section: Discussionmentioning
confidence: 61%
“…Victoria blue staining revealed the disappearance of elastic fibers, degeneration of vascular muscle cells and a significant increase in collagen fibers, in agreement with human AAA pathological conditions. Previous findings have shown that inflammation plays an important role in the pathogenesis of AAA and the regulation of monocyte-macrophage cells, lymphocyte activation and migration by chemokine is one of the key steps to develop AAA (11,12). Additionally, the expression of chemokines was significantly increased in AAA patients and macrophages as well as lymphocytes in blood infiltrating the arterial wall when induced by chemokines, causing the release of excess MMP and further degradation of structural proteins (elastin, collagen) in the aorta wall and damage of elastic fibers and collagen fibers (13).…”
Section: Discussionmentioning
confidence: 99%